Recognition and catabolism of synthetic heterotrimeric collagen peptides by matrix metalloproteinases. - Ottl, J; Gabriel, D; Murphy, G; Knäuper, V; Tominaga, Y; Nagase, H; Kröger, M; Tschesche, H; Bode, W; Moroder, L (2000)
BACKGROUND: The general consensus is that interstitial collagens are digested by collagenases and denatured collagen by gelatinases, although processing of fibrillar and acetic-acid-soluble collagen by gelatinase A has also been reported. One of the main difficulties in studying the mechanism of action of these matrix metalloproteinases (MMPs) derives from the physicochemical properties of the natural triple-helical collagen, which makes it difficult to handle. RESULTS: Synthetic heterotrimeric collagenous peptides that contain the collagenase cleavage site of human collagen type I and differ in the thermal stability of the triple-helical fold were used to mimic natural collagen and gelatin, respectively. Results from digestion of these substrates by fibroblast and neutrophil collagenases (MMP-1 and MMP-8), as well as by gelatinase A (MMP-2), confirmed that the two classes of enzymes operate within the context of strong conformational dependency of the substrates. It was also found that gelatinases and collagenases exhibit two distinct proteolytic mechanisms: gelatinase digests the gelatin-like heterotrimer rapidly in individual steps with intermediate releases of partially processed substrate into the medium, whereas collagenases degrade the triple-helical heterotrimer by trapping it until scission through all three alpha chains is achieved. CONCLUSIONS: The results confirm the usefulness of synthetic heterotrimeric collagenous peptides in the folded and unfolded state as mimics of the natural substrates collagen and gelatin, respectively, to gain a better a insight into the proteolytic mechanisms of matrix metalloproteinases.